Tentoonstelling van Moppes, Albert Cuypstraat. Geopend maart 1955. Burgemeester van Amsterdam d'Ailly (1955)
Tentoonstelling van Moppes, Albert Cuypstraat. Geopend maart 1955. Burgemeester van Amsterdam d'Ailly.